Affective Commitment in Mediating Organizational Citizenship Behavior Factors in XYZ Hospital Staff in Tana Toraja - Karina Maharati Wibowo; Oscar Jayanagara (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The increasing number of private hospitals must be balanced with the quality of hospital human resources. This research was conducted to determine the influence of psychological empowerment, psychological capital, work engagement on organizational citizenship behavior which is mediated by affective commitment in XYZ Hospital officers in Tana Toraja. The research was quantitative and conducted cross-sectionally. The total sample was 155 officers. The sample was selected using probability sampling, namely simple random sampling. Research data was taken using Google form media with five answer choices. The data analysis method uses PLS-SEM. The results of this study found that psychological empowerment and work engagement have no effect on organizational citizenship behavior. Psychological capital and affective commitment each have a significant positive effect on organizational citizenship behavior. Psychological empowerment, psychological capital, work engagement each have a significant positive effect on affective commitment. Affective commitment fully mediates the influence of psychological empowerment on organizational citizenship behavior. Affective commitment partially mediates the influence of psychological capital on organizational citizenship behavior. Affective commitment fully mediates the influence of work engagement on organizational citizenship behavior. This research was conducted only in one hospital in Tana Toraja. Future research can use several hospitals in Tana Toraja so that it can be generalized more widely. The management of XYZ Tana Toraja Hospital can improve the organizational citizenship behavior of its officers through factors such as psychological empowerment, psychological capital, work engagement, and affective commitment.